Kemampuan Technological Pedagogical Content Knowledge (TPACK) Calon Guru Biologi Fkip Ums Dalam Menyusun Rpp Kurikulum 2013 Tahun Akademik 2016/2017 - Dhawati, Dwi Anis Aris; , Dra. Hariyatmi, M.Si (2017)
Teachers are the main factors and determine the ( a key ) the success of learning and efforts renewal the quality of education .The world as the technology a teachers and pre-servise teacher must also be able to follow the developments tech to create learning more effective , efficient and innovative. Technological Pedagogical Content Knowledge ( TPACK ) described knowledge synthesized from each sector knowledge described above ( TK , CK , IS , PCK , TCK , TPK ) with a focus to ways of how technology could made with typical for faced with pedagogis needs to teach content right moment in a given context. Every element of this field describing a the needs and the importance of these aspects in teaching. Research aims to understand TPACK picture pre-servise teacher Departement of Biology Education Muhammadiyah University of Surakarta in preparing lesson plans 2013 curriculum academic year 2016 / 2017. The kind of research used descriptive qualitative with strategy of case study. Research methodology used the documentation , technique data collection in research this is the method documentation with way to a 120 lesson plans from 60 pre-servise teacher where each pre-servise teacher was taken two servise techer lesson plans. Technique data analysis that is by means of tabulated later identified and served in a form of sentence descriptive. The results of the reseacrh showed that the TPACK with a large percentage the best (81,18 %). Based on the results of reseach can be concluded that the TPACK pre-servise teacher Departement of Biology Education Muhammadiyah University of Surakarta is good.